(untitled) - Kieso, Donald E. (Hoboken, N.J., 2003)
Now you can get all the accuracy, authority, and student success of the best-selling intermediate accounting text in a brief, streamlined new version! The authors have made tough decisions about what material remains at the core of the intermediate accounting course, and what details (for example, methods of depreciation) are less important for today's student. The result of their work is the briefest two/three-semester intermediate text on the market. This new streamlined size will also allow you to introduce case material or special readings as you choose.
Keywords: Accounting,Kế toán